2006
DOI: 10.1159/000092233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Rinsing Protocols after the Use of Amine Fluoride/Stannous Fluoride Toothpaste on the Acid Production of Dental Plaque and Tongue Flora

Abstract: The aim of this clinical study was to evaluate the effect of various rinsing protocols on oral acid production 6 h after tooth brushing with an amine fluoride/stannous fluoride (AmF/SnF2) toothpaste. After a 14-day period of using F-free toothpaste, 30 participants followed three experimental protocols each, followed by F-free washout periods in a randomized crossover trial. They used AmF/SnF2 toothpaste twice daily for 1 week, and after brushing, they either rinsed with tap water, omitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…The concentration of lactic acid in the tongue coating is known to reach 6.7 to 7.8 mM after a sucrose rinse (26,27) due to the dominance of lactate-producing bacteria such as streptococci (5) and probably results in acidification of the tongue coating. Thus, in the tongue coating, changes in both pH and the lactate concentration may influence H 2 S production by Veillonella.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of lactic acid in the tongue coating is known to reach 6.7 to 7.8 mM after a sucrose rinse (26,27) due to the dominance of lactate-producing bacteria such as streptococci (5) and probably results in acidification of the tongue coating. Thus, in the tongue coating, changes in both pH and the lactate concentration may influence H 2 S production by Veillonella.…”
Section: Discussionmentioning
confidence: 99%
“…Even though not all acidogenic organisms decreased in proportion (in particular, S. mutans and Lactobacilli did not), the data suggest that the plaque had turned less cariogenic. Gerardu et al [2006] have shown that the protocol of AmF/SnF 2 toothpaste + AmF/SnF 2 rinse reduced plaque acidogenicity, which may now be related to a reduced proportion of some acidproducing bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…A full description of the subjects, experimental design, oral hygiene protocols, toothpastes, rinses and sampling can be found in Gerardu et al [2006]. In brief, after a 2-week period of using a NaF toothpaste (Prodent Cool Mint 1,450 ppm F; Sara Lee, Veenendaal, The Netherlands) and a 2-week fluoride-free toothpaste (Ultradent; Kruidvat, Renswoude, The Netherlands) period, 30 volunteers (22 women, 8 men; mean age: 26.8 8 7.3 years) were enrolled in a randomized crossover examiner-blind controlled clinical trial with 1-week experimental periods each followed by a 2-week fluoride-free washout period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations